Maskot Asian Para Games 2018: Identitas dan Aplikasinya - Hadiprawiro, Yulianto; Hidayati, Atiek Nur (Magenta | Official Journal STMK Trisakti, 2019)
The 2018 Asian Para Games is a continent-level disability sports event that involves many athletes with disabilities in various sectors in the community at large. Indonesia hosted the sporting event for Difabel in 2018. As one of the international sports parties, in 2018, the Asian Para Games issued visual promotions to support the promotion needs of the event. Uniquely, the promotion form of the 2018 Asian Para Games is also supported by mascots and logos that resemble the 2018 Asian Games. Indirectly this supports the visual promotion of the Asian Para Games 2018. Campaign materials that are compatible with diffable entities are also needed as visual markers for a grand event like Asian Para Games 2018. Research discusses campaign material, focusing on mascot and visual production of derivatives from mascot. This aims to see how the 2018 Asian Para Games mascot becomes an important part of the visual promotion that is disseminated to the public. The visual representation that emerges will provide knowledge that in the Asian Para Games program, mascot is needed to support its visual promotion massively. This study found; (1) definition and history of bondol eagle mascot as the mascot of the Asian Para Games 2018; (2) The forms of visual mascot applications that appear have represented the Asian Para Games event, although they have not represented the visuals of Difabel. ABSTRAK Asian Para Games 2018 merupakan ajang olahraga difabel tingkat benua Asia yang melibatkan banyak atlet disabilitas diberbagai sektor di masyarakat secara luas. Indonesia menjadi tuan rumah dalam ajang perhelatan olahraga bagi Difabel pada tahun 2018. Sebagai salah satu pesta olahraga internasional, pada tahun 2018, Asian Para Games mengeluarkan promosi-promosi secara visual guna mendukung kebutuhan promosi terhadap acara tersebut. Uniknya, bentuk promosi Asian Para Games 2018 juga didukung oleh maskot dan logo yang menyerupai Asian Games 2018. Secara tidak langsung hal ini mendukung promosi visual Asian Para Games 2018. Materi kampanye yang sesuai dengan entitas difabel juga dibutuhkan sebagai penanda visual sebuah acara akbar layaknya Asian Para Games 2018. Penelitian membahas tentang materi-materi kampanye, dengan berfokus pada maskot dan produksi visual turunan dari maskot. Hal ini bertujuan untuk melihat bagaimana maskot Asian Para Games 2018 menjadi bagian penting dalam promosi visual yang disebarkan ke masyarakat. Representasi visual yang muncul akan memberikan pengetahuan bahwa dalam acara setingkat Asian Para Games, memang diperlukan maskot untuk mendukung promosi visualnya secara masif. Penelitian ini menemukan; (1) definisi dan sejarah maskot burung elang bondol sebagai maskot Asian Para Games 2018; (2) Bentuk-bentuk aplikasi visual maskot yang muncul sudah merepresentasikan acara Asian Para Games, meskipun belum mewakili visual Difabel.